Atrial Fibrillation and Use of Rivaroxaban: Performance of the Prothrombin Time / INR as a Function of Time After Blood Collection - Duarte,Rita Carolina Figueiredo (2021)
Abstract Background Traditionally, the most effective therapy in the prevention of stroke in patients with atrial fibrillation (AF) has been oral anticoagulation with vitamin K inhibitors, particularly warfarin, whose disadvantages and adverse effects have led to their replacement by "direct oral anticoagulants", as factor X inhibitor. Objectives This study aimed to conduct a brief approach on atrial fibrillation (AF) and use of Rivaroxaban, and to comparatively evaluate the prothrombin time / International Normalized Ratio (PT/INR) in patients with AF in use of this oral anticoagulant, depending on the time elapsed between the last administration of the drug and the time of blood sample venipuncture. Methods We evaluated 34 patients with AF in use of Rivaroxaban by using PT / INR, distributed into a subgroup with blood collection time ≤ 12 hours (n = 7) and > 12 hours after the last drug intake (n = 27). Mann-Whitney test was used to compare the groups and p < 0.05 was considered significant. Results An analysis as a function of time between the Rivaroxaban intake and blood collection, revealed that PT / INR suffers the greatest effect up to 12 hours after ingestion of the drug, dropping to levels close to normal in subsequent hours before the next dose. Conclusion We concluded that, in contrast to warfarin, the knowledge of the time interval between drug intake and blood collection from patients taking Rivaroxaban is essential to properly interpret a laboratory test to assess hemostasis, particularly PT and its derivatives. Int J Cardiovasc Sci. 2020; [online].ahead print, PP.0-0